Attitudes About Wife Beating: A Comparison of Medical Students and Arts Students - McCall, Marnie A.; Webber, Gail (Université d'Ottawa | University of Ottawa, 1994)
An inventory of beliefs about wife beating was used to compare the attitudes of medical students and arts students to woman abuse. Data were collected from 66 first year medical students, 56 third year medical students, and 66 arts students. All groups showed similar relatively sympathetic attitudes overall toward battered women, and there was no significant difference in the three groups. Age, education, marital status, and personal or close experience with abuse did not affect attitudes. Female respondents were shown to be statistically more sympathetic to battered women than men in two of the three subscales, but the scores were so close that this may not translate into a clinically significant finding.